Inclusión de la ética en la formación del estudiante de enfermería en una universidad privada - Cervera Vallejos, Mirtha Flor (2010)
Descriptive qualitative study, that had as objectives to describe, analyze and discuss ethics on undergraduate nursing education. Polo (2006,2007), Domínguez (2005) y Waldow (2004-2008) were the authors that offered the theoretical support to the study. The setting was the Nursing School of Santo Toribio de Mogrovejo University located in Chiclayo - Perú. The sample was get through saturation, using as a gathering data the semi-structured interview with previous informed consent, to 9 teachers from core subjects and 9 students of the ninth cycle. The thematic analysis of content generated 3 categories: Concept of ethics training with its subcategories: As self-knowledge, as an imperative to care for others; as living in care. The territory of ethics in training with its subcategories: Linking up / Dissociation of theoretical ethical knowledge with practical ethical knowledge; personalizing / trivializing the subject against the requirement for personalized education; fragmentation / integration of teacher-student relationship. Modeling ethics training, with their subcategories: Being teacher, showing an ethical act; an act to be a student modeling ethical care practices. As final considerations, education on ethics must include self knowledge, know how to coexist, be models with a coherent ethical life and learn together, otherwise there will be problems, mistrust, poor dialogue, lack of openness, Dissociation of theoretical ethical knowledge and ethical practice and trivialization of the subject